Varia Dabt Mushaf Al-Qur’an Qiraat Abu 'Amr Riwayat Ad-Duriy - Qinta Berliana Valfini; Muhammad Aminullah; Rahmat Taufik Sipahutar; Osman Nuhu Sharubutu (Lajnah Pentashihan Mushaf Al-Qur'an, 2025)
The science of dabt was developed to preserve the authenticity of Qur’anic recitation as Islam spread into non-Arab regions. However, its application in modern mushafs reveals certain inconsistencies. This study aims to examine these inconsistencies through a comparative analysis of the dabt system in three mushafs of the Qur’anic reading (qira'a) of Abu 'Amr, transmitted by ad-Duri, namely the editions from Madinah, Sudan, and the digital version of at-Taysir. Employing a descriptive-comparative method, the research identifies and analyzes the patterns of similarities and differences in diacritical marks among the three mushafs. The findings indicate uniformity in the fundamental elements of dabt, such as basic vowels (harakat), sukun, and tasydid, which largely follow the system of al-Khalil ibn Ahmad al-Farahidiy. However, significant variations are observed in markings such as imala, alif wasl, and the treatment of isqat. The study concludes that uniformity is primarily driven by the shared rasm and qira'a, while diversity arises from differences in dabt schools (masyriqiy and magribiy), the evolution of mediums (print and digital), and local scholarly ijtihad. This research underscores that the variations in dabt reflect the socio-cultural dynamics within the tradition of safeguarding the Qur'anic text.